2019
DOI: 10.1002/fee.2073
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA in lake sediment reveals biogeography of native genetic diversity

Abstract: Understanding the historical distributions of species is vital to the conservation and restoration of native species, yet such information is often qualitative. We show that the paleolimnological history of threatened freshwater fishes can be reconstructed using species‐diagnostic markers amplified from environmental DNA deposited in lake sediments (lake sedDNA). This method was validated through the detection of lake sedDNA from non‐native trout (Yellowstone cutthroat trout, Oncorhynchus clarkii bouvieri), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…By using the sedDNA approach, we detected anchovy, sardine, and jack mackerel DNA from sediment layers dating back 300 years, confirming that fish DNA can be detected from marine sedimentary sequences. Our finding supports the long-term preservation potential of macro-organism DNA in the sediments of marine systems, as well as freshwater systems as previously reported 3 , 6 , 7 , even though aquatic and bottom environments are completely different in marine and freshwater systems (e.g., salinity, pH, light, and tidal effects).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By using the sedDNA approach, we detected anchovy, sardine, and jack mackerel DNA from sediment layers dating back 300 years, confirming that fish DNA can be detected from marine sedimentary sequences. Our finding supports the long-term preservation potential of macro-organism DNA in the sediments of marine systems, as well as freshwater systems as previously reported 3 , 6 , 7 , even though aquatic and bottom environments are completely different in marine and freshwater systems (e.g., salinity, pH, light, and tidal effects).…”
Section: Discussionsupporting
confidence: 92%
“…At present, only a very few studies have been conducted on the sedDNA of macro-organisms. These studies investigated a variety of subjects; i.e., major changes in species composition 4,5 , extinct biota 4,5 , livestock farming history associated with the Anthropocene 3 , and the identification of a taxon as a native or alien fish species in lake ecosystems 6,7 . These studies demonstrated that sedDNA is a potentially powerful tool that could be used to detect the "presence/absence" of a taxon and reconstruct past species compositions for macro-organisms.…”
mentioning
confidence: 99%
“…Thus far, the most common investigated aquatic organisms in sedaDNA studies have been photosynthetic bacteria and phytoplankton [18,34,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81]. Although macrophytes and some algal groups are typically well detected in sedaDNA plant surveys [24][25][26]81,82], there are few papers reporting the presence of zooplanktonic DNA [83,84] and fish DNA from lake sediments [85][86][87].…”
Section: Sedadna To Unravel Past Diversity and Composition Of Lake Biotamentioning
confidence: 99%
“…Much of that research has been targeted to species for which the body remains in the sample, such as bacteria (Domaizon et al, 2013), other microbes (Hou et al, 2014), and plants (Pansu et al, 2015), or species for which part of the body, such as bones, are preserved (Wooller, Gaglioti, Fulton, Lopez, & Shapiro, 2015). More recently, studies have been developed to detect macro-organisms using extracellular DNA remaining in sediments (i.e., sedimentary eDNA), for example, for fish (Nelson-Chorney et al, 2019;Stager, Sporn, Johnson, & Regalado, 2015). These studies showed that fish sedimentary eDNA can be detected in sediments from ~140 years ago.…”
Section: Introductionmentioning
confidence: 99%